(untitled) (Italian Review of Legal History, 2021)
The essay intends to examine the characteristics of the Milanese notary profession in the delicate moment of transition from the ancient regime to the subsequent Napoleonic age, when the ideology of the Revolution, exported by the Napoleonic armies, involved, in the specific notary sector, the abandonment of the heterogeneous functions that had characterized the eighteenth-century notaries, in a continuous balance between ‘private’ and ‘public’, and the affirmation of a series of new, fundamental principles. With the “legal revolution” that Napoleon introduced in Italy in the field of professions, an unprecedented transformation was achieved, even in the notarial sector. The suppression of professional colleges and corporations put an end to the age-old monopoly of qualifications, now liberalized both in relation to private and public activities. Any distinction between noble and bourgeois professions was canceled with the formal birth of the liberal professions. In particular, the case of Milan will be studied: Milan, after having experienced some important changes at the end of the ancien régime, such as the birth of the public archive (1775), the Joseph II’s reform of the recruitment of notaries and the Regolamento generale per i notari della Lombardia austriaca (1794), lived, first as the capital of the Napoleonic Kingdom of Italy and then in the political reality of the Lombardo-Venetian Kingdom, an intense season of lively debates on the opportunity and methods of innovating a profession, for some time exercised in a protean manner by a class, anything but compact, in which very different operators were distinguished from each other in terms of culture and social origin. The Regolamento sul Notariato of the Kingdom of Italy, published on 17 June 1806, took up the discipline of the Regolamento generale per i notari della Lombardia austriaca and differed in some points from the French notarial law. Still in force after the fall of Napoleon, the Regolamento sul Notariato of 1806 was also an alternative model to French law in the Kingdom of Lombardy-Venetia, where, for a certain period, there was discussion on whether to maintain or abolish the notary profession. The Austrian civil code, applied in the Lombardo-Venetian Kingdom, did not regulate the figure of the notary by law and the Austrian domination did not leave great autonomy to the notaries. However, without apparently suffering the frenetic political upheavals of the first half of the nineteenth century, the Lombard notaries proved to be an industrious category, capable of adapting to the new times, no longer held back in their social and professional rise by the constraints imposed by the ancient society regime. Despite the numerous studies conducted, in recent and less recent times, on notaries in the modern age, the subject is far from exhausted and, thanks to the rich documentary heritage preserved in the archives, it is possible and desirable to expand research on the specific reality of the nineteenth-century Lombard notary, which, in a period so full of changes, was going through an important process of professionalization. This process, after the Restoration, was defined in a precise manner and notaries became fully qualified professionals capable of aspiring to the most important city offices.